Energy Management in Hybrid Renewable Systems - Jove, Esteban; Díaz-Longueira, Antonio; Arcano-Bea, Paula; Timiraos, Míriam; Michelena, Álvaro; Zayas-Gato, Francisco; Quintián, Héctor; Casteleiro-Roca, José-Luis; Calvo-Rolle, José Luis (EASI: Engineering and Applied Sciences in Industry, 2023)
This document focuses on the analysis of solutions to the need to design the feeding system of a modular and mobile installation in charge of monitoring the water quality of a river. This problem, arising from the proposal of a research project of the Ministry of Science and Innovation of the Government of Spain, aims to supply the consumption caused by both the water acquisition system, thermal conditioning of the facility, electronics, and instrumentation, as well as such as telecommunications equipment to upload measurements to the cloud.